Processor Design System-on-Chip Computing for ASICs and FPGAs - Nurmi, Jari.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Processor Design addresses the design of different types of embedded, firmware-programmable computation engines. Because the design and customization of embedded processors has become a mainstream task in the development of complex SoCs (Systems-on-Chip), ASIC and SoC designers must master the integration and development of processor hardware as an integral part of their job. Even contemporary FPGA devices can now accommodate several programmable processors. There are many different kinds of embedded processor cores available, suiting different kinds of tasks and applications. Processor Design provides insight into a number of different flavors of processor architectures and their design, software tool generation, implementation, and verification. After a brief introduction to processor architectures and how processor designers have sometimes failed to deliver what was expected, the authors introduce a generic flow for embedded on-chip processor design and start to explore the vast design space of on-chip processing. The types of processor cores covered include general purpose RISC cores, traditional DSP, a VLIW approach to signal processing, processor cores that can be customized for specific applications, reconfigurable processors, protocol processors, Java engines, and stream processors. Co-processor and multi-core design approaches that deliver application-specific performance over and above that which is available from single-core designs are also described. The special design requirements for processors targeted for FPGA implementation, clock generation and distribution in microprocessor circuits, and clockless realization of processors are addressed. Tools and methodologies for application-specific embedded processor design are covered, together with processor modelling and early estimation techniques, and programming tool support for custom processors. The book concludes with a glance to the future of embedded on-chip processors.
Embedded Computer Architecture Fundamentals -- Beyond the Valley of the Lost Processors: Problems, Fallacies, and Pitfalls in Processor Design -- Processor Design Flow -- General-Purpose Embedded Processor Cores - The COFFEE RISC Example -- The DSP and Its Impact on Technology -- VLIW DSP Processor for High-End Mobile Communication Applications -- Customizable Processors and Processor Customization -- Run-Time Reconfigurable Processors -- Coprocessor Approach to Accelerating Multimedia Applications -- Designing Soft-Core Processors for FPGAs -- Protocol Processor Design Issues -- Java Co-Processor for Embedded Systems -- Stream Multicore Processors -- Processor Clock Generation and Distribution -- Asynchronous and Self-Timed Processor Design -- Early-Estimation Modeling of Processors -- System Level Simulations -- Programming Tools for Reconfigurable Processors -- Software-Based Self-Testing of Embedded Processors -- Future Directions in Processor Design.
Keywords: ENGINEERING; COMPUTER NETWORK ARCHITECTURES; COMPUTER SCIENCE; SOFTWARE ENGINEERING; SYSTEMS ENGINEERING; ENGINEERING; CIRCUITS AND SYSTEMS; PROCESSOR ARCHITECTURES; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS; SPECIAL PURPOSE AND APPLICATION-BASED SYSTEMS; COMPUTER SYSTEM IMPLEMENTATION